Participação social e alternativas de desenvolvimento na Transamazônica: a ONG ASSEEFA o os PDSs de Anapu-PA - SOUSA, Fledys do Nascimento (Universidade Federal do Pará, 2014)
This thesis discusses the alternatives for the Transamazonica Road development, from studies of the Non-Governmental Organization named Associação Solidária e Econômica de Frutas da Amazônia (ASSEFA) that is responsible by the Projetos de Desenvolvimento Sustentável (PDSs), in the municipal district of Anapu, Transamazônica, Pará State. It objectifies, verify the images built about ASSEEFA and PDSs and, thus, point the participation civil society degree of Anapu in the development alternative politicses formulation and implementation process at that region. It objectifies, yet, turn explicit where field built the references to the environment, present in the social actions locations fights. Do take like reference the concepts introduced for Ammann (1978) and Bordenave (1994), we question the existence or not of social participation in ASSEEFA's creation and in PDSs' implementation? In this sense, the social categories participation, civil society, development, environment and Amazônia, with latent reflexes in this region, were going selected like analysis central elements, what it is accomplished soon in the first chapter. With the intent of offering at the height of the objective answers above pointed, it analyzed, by means of bibliographical research and of field, first moment, the constitution trajectory of ASSEEFA and of PDSs. It observed, thus, that, in the partnerships, civil society disputes and negotiations, there were important components that evidenced that those actions own directed proposals to a development type that valorizes the environment and that, above all, it pledges with the citizenship ransom. The points of view government institutions analysis like Instituto Nacional de Colonização e Reforma Agrária (INCRA) and Instituto Brasileiro do Meio Ambiente e dos Recursos Naturais Renováveis (IBAMA) and lumbermen association representatives, it served like reference for several possibilities comprehension, interests and conflicts with that are introduced the civil society initiatives and the development accomplishment in Transamazônica. We take like main hypothesis the formulation that the social participation in ASSEEFA and in PDSs de Anapu is tied to more several interests and that this means a breaking with old practices and visions on the development and the possibility of these farming of warranty of her effective freedoms, as the right to land, to work, the education and to the health, in short to the human being's fundamental rights.